Characterization of a Novel Chromosome-Encoded AmpC β-Lactamase Gene, blaPRC–1, in an Isolate of a Newly Classified Pseudomonas Species, Pseudomonas wenzhouensis A20, From Animal Farm Sewage - Zhang, Peiyao; Dong, Xu; Zhou, Kexin; Zhu, Tingting; Liang, Jialei; Shi, Weina; Gao, Mengdi; Feng, Chunlin; Li, Qiaoling; Zhang, Xueya; Ren, Ping; Lu, Junwan; et al. (Frontiers in Microbiology, 2021)
In this work, we characterized a novel chromosome-encoded AmpC β-lactamase gene, blaPRC-1, in an isolate of a newly classified Pseudomonas species designated Pseudomonas wenzhouensis A20, which was isolated from sewage discharged from an animal farm in Wenzhou, China. Susceptibility testing, molecular cloning and enzyme kinetic parameter analysis were performed to determine the function and enzymatic properties of the β-lactamase. Sequencing and comparative genomic analysis were conducted to clarify the phylogenetic relationship and genetic context of the blaPRC-1 gene. PRC-1 is a 379-amino acid AmpC β-lactamase with a molecular weight of 41.48 kDa and a predicted pI of 6.44, sharing the highest amino acid identity (57.7%) with the functionally characterized AmpC β-lactamase PDC-211 (ARX71249). blaPRC-1 confers resistance to many β-lactam antibiotics, including some penicillins (penicillin G, amoxicillin and amoxicillin-clavulanic acid) and cephalosporins (cefazolin, ceftriaxone and cefotaxime). The kinetic properties of PRC-1 were compatible with those of a typical class C β-lactamase showing hydrolytic activities against β-lactam antibiotics, and the hydrolytic activity was strongly inhibited by avibactam. The genetic context of blaPRC-1 was relatively conserved, and no mobile genetic element was predicted in its surrounding region. Identification of a novel β-lactamase gene in an unusual environmental bacterium reveals that there might be numerous unknown resistance mechanisms in bacterial populations, which may pose potential risks to human health due to universal horizontal gene transfer between microorganisms. It is therefore of great significance to carry out extensive research on the mechanism of antibiotic resistance.